The Depiction of Heaven and Hell in the Karmawibangga Reliefs of Borobudur Temple: An Overview of Character Education - Iswahyudi Iswahyudi (RIRAI Publisher, 2021)
Karmawibhangga comes from the words karma and wibhangga. If karma can literally be interpreted as actions that come from causes and cause effects, then wibhangga is a designation for one of the holy books in Buddhism (Buddhist scripture). Literally karma can be interpreted as actions that come from causes and cause effects. In Buddhism, karma is the basic doctrine formulated and taught by Siddhartha Gautama. According to this doctrine, every living being has karma, both generated by himself and inherited from his ancestors. It is this karma that has caused samsara and is a barrier to attaining heaven or nirvana. Births in heaven and in hell seem to be at the core and there is a belief that some kind of hell is known in written sources both inscriptions and ancient manuscripts in Java. The state of life in heaven is marked by the kalpawrksa tree flanked by kinaras.